Inhibitory effects of Pueraria mirifica aqueous extracts on 5α-reductase and prostate histomorphometry in testosterone induced benign prostatic hyperplasia Sprague Dawley rats - Masrudin, Siti Saleha; Razwan, Nur Izzah Athirah; Mat Taib, Che Norma; Mohd Nor, Nurul Huda; Mohd Asri, Siti Fadziyah; Alias, Zazali; Mohamad, Jamaludin (Faculty of Medicine and Health Sciences, UPM, 2023)
Introduction: Benign prostatic hyperplasia (BPH) is the most prevalent prostatic disease in ageing men, characterised by an excessive proliferation of the prostatic epithelial and stromal cells. Despite the extensive choices of pharmaceutical therapies, the current treatments possess side effects, necessitating the search for new alternative options, including herbal substances such as Pueraria mirifica. This tuberous root of P. mirifica is a medicinal plant that contains numerous phytoestrogens, traditionally used for health rejuvenation in aged men and women. This study was carried out to access the inhibitory effect of 5α-reductase of P. mirifica and its histoprotective effect in a rat model of testosterone-induced BPH. Methods: Adult Sprague Dawley (12 weeks) were subcutaneously injected with testosterone propionate (3 mg/kg) daily to induce BPH. Rats (n=6) in all groups (aqueous extract of P. mirifica (APM): 10, 100, and 1000 mg/kg, p.o.; finasteride: 2mg/kg, p.o., BPH model, and sham groups) were treated for 30 days. The determination of serum dihydrotestosterone (DHT) level, prostatic index and prostate structural changes were investigated. Results: APM and finasteride-treated groups showed significantly lesser prostatic weight and prostatic index, serum DHT levels compared to the model group (p<0.05). Furthermore, there was a significantly lower prostate score with improved prostate histomorphology, demonstrating fewer epithelial involutions of glandular tissues and improved stromal and epithelial cells. Conclusion: In conclusion, the aqueous extract of P. mirifica tuberous root mitigates the development of BPH and it can be inferred that aqueous extract of P. mirifica tuberous root may possess the active agents for anti-BPH treatment.